The effect of salicylic acid priming on improvement of germination characteristics, activity of antioxidant enzymes and membrane lipid peroxidation of wheat under salinity conditions - Ahmad Afkari (علوم و فناوری بذر ایران)
In order to investigate the effects of priming with salicylic acid and salinity stress on improvement of germination characteristics, activity of antioxidant enzymes and and membrane lipid peroxidation of wheat cultivar Mihan, an experiment was conducted as factorial in a completely randomized design with three replications in the physiology lab at the Islamic Azad University of Kaleiber Branch in 2018.The treatments consisted of different concentrations of acid salicylic in four levels (0, 0.5, 1 and 1.5 mM) and salt stress was inducted by NaCl solution (0, 50 100, 150 mM). The results analysis of variance showed that the effects of salinity and salicylic acid on germination indices and activity of antioxidant enzymes was significant.Results comparison of data showed that NaCl priming by salicylic acid increased the germination percentage, root growth, root, seedling dry weight and decreasing activity of antioxidant enzymes and seed protein content in the salty environment. Salicylic acid increased the level of cell division of seedlings and roots which caused an increase in plant growth. Enzymes activity assay showed that enzyme activity was increased under salt stress conditions and SA reduced activity of antioxidant enzyme by decreasing the salinity effects. In brief, the SA treatment reduced the damaging action of salinity on seedling growth and accelerated a restoration of growth processes. It seems that Salicylic acid as a plant growth regulator under salinity condition, activated plant tolerance mechanisms to salinity condition and decrease damaging effect of salinity on seed germination and seedling growth of wheat.